2005
DOI: 10.1136/adc.2004.061986
|View full text |Cite
|
Sign up to set email alerts
|

What do parents think about enrolling their premature babies in several research studies?

Abstract: Objective: To investigate parents' opinions about enrolling their premature baby into several research studies in the few days after birth. Methodology: A questionnaire was given to parents of premature babies in the neonatal intensive care unit who had been invited to join several studies (two to seven). Results: All 50 mothers and 42 of 48 fathers completed the questionnaire independently; 28% had been asked to join two studies, 32% three, 24% four, 14% five, and 2% six studies. There were 61 babies with mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 14 publications
4
58
1
1
Order By: Relevance
“…A pediatric study supports that 32% of parents of critically ill infants would prefer to have their physician advise them as to whether their baby should participate in a neonatal ICU trial rather than being asked to decide themselves. 11 In a study 12 of adults, researchers reported that 35% of family members of critically ill patients experience symptoms of posttraumatic stress associated with requests to provide consent for research participation. Compared with involvement of any physician, respondents preferred their attending physician to be involved in decisions regarding their participation in research.…”
Section: Discussionmentioning
confidence: 99%
“…A pediatric study supports that 32% of parents of critically ill infants would prefer to have their physician advise them as to whether their baby should participate in a neonatal ICU trial rather than being asked to decide themselves. 11 In a study 12 of adults, researchers reported that 35% of family members of critically ill patients experience symptoms of posttraumatic stress associated with requests to provide consent for research participation. Compared with involvement of any physician, respondents preferred their attending physician to be involved in decisions regarding their participation in research.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Consent can often be sought soon after diagnosis, at birth or when the child is very ill and the parents are distressed and vulnerable. 30,45,46 Despite such challenges, parents have reported that they, rather than doctors or nurses, should be the ones who make the decision about whether a child should enter a trial, 15,32,43,47,48 although parents value doctors' advice. 49 Making a decision for one's child is further complicated by the need to make the 'right decision' and the anticipation that one might later regret a decision.…”
Section: The Context and Experience Of Trial Recruitmentmentioning
confidence: 99%
“…However, Morley et al 15 showed 74% of parents would be happy to join two or more studies. In a model proposed for obtaining informed consent, Golec et al 17 suggest that, if a parent is to be approached for more than one study, these requests should be made at least 48 hours apart.…”
Section: Ethical and Legal Issuesmentioning
confidence: 99%